The Impact of Research and Development for Business Innovations in Lithuania - Dalia Streimikiene (Amfiteatru Economic Journal, 2014)
The paper aims to assess the impact of research and development on innovativeness of the country as research and development is one of the main drivers of economic development and creation of modern knowledge based economy stipulating efficient use of natural resources and reducing negative impact on environment. The paper analyzes the main Lithuanian policy documents aiming at promotion of knowledge economy, innovations and research and development and financing of research, technological development and innovation. The programmes aiming at modernization of enterprises and trends of sustainable industrial development in Lithuania are critically reviewed. The Summary Innovation Index (SII) of Lithuania was applied to assess the impact of implementing policies promoting research and development in Lithuania. The analysis indicated that one of the main factors determining the relatively low Lithuanian SII is the insufficient level of investment in research and development (R&D). While R&D expenditure in the general government and higher education sectors corresponds to the EU average, it remains low in the business sector.
Keywords: L2; L26; L53; O32; O35; 330; research and development; sustainable industrial development; modernization of enterprises; innovation index